Development of a continuous professional development training module based on multicultural counselling competency for professional counsellors in Malaysia - Rafidah Aga, Mohd Jaladin; Noh, Amit; Azad Athahiri, Anuar; Janet Ann, Fernandez; Sakinah, Salleh; Haniza, Rais; Haslee Sharil, Lim (SAGE Publications, 2019)
The aim of this study was to develop a continuous professional development training module based on multicultural counselling competency for professional counsellors in Malaysia. The research methodology comprised three phases: (i) training need assessment using survey method, (ii) module design and development and (iii) module evaluation using an experimental design. First, the Multicultural Counselling Competency Survey-Malaysian Counsellor Edition questionnaire was used to collect data from 116 professional counsellors from various work settings. The results clearly indicated the need for continuous professional development training to enhance counsellors’ multicultural counselling competency. The development of the training module adopted Sidek’s model, a Malaysian-based framework for module development. The developed training module was then evaluated for its effectiveness through analysing its content validity and reliability. Results revealed that the training module scored high content validity value of 77.2% (0.77) and satisfactory reliability level (alpha Cronbach’s coefficient value of 0.75). The overall findings of the present research imply that the continuous professional development training module is necessary for enhancing multicultural counselling competency of Malaysian professional counsellors.